Penerapan Media Power Point Untuk Memperluas Pemahaman Siswa Kelas VIII B Pada Mata Pelajaran Pendidikan Agama Islam di SMP Negeri Rasau Jaya 1 Kubu Raya - Muhammad Basarrudin (FAKULTAS TARBIYAH INSTITUT AGAMA ISLAM SULTAN MUHAMMAD SYAFIUDDIN SAMBAS, 2023)
This research aims to design learning using PowerPoint to improve class VIII B students' understanding of PAI subjects, describe and analyze how to apply to learn using PowerPoint to improve class VIII B students' knowledge of PAI subjects and define and explore how to assess learning using Powerpoint to enhance the understanding of class VIII B students in the PAI subject at SMP Negeri Rasau Jaya 1 Kubu Raya. It can apply effective learning materials to improve the knowledge of students at SMP Negeri Rasau Jaya 1 Kubu Raya Class VIII B in the subject of PAI. This research method uses qualitative with the type of classroom action research. The study is divided into four phases: design, implementation, observation, and reflection. The research results on learning planning using PowerPoint as a learning tool begin with defining the topic, preparing learning, preparing PowerPoint media, and preparing test questions and means (LCD). Applied knowledge with PowerPoint runs smoothly and according to predetermined plans. Learning assessment using PowerPoint media takes place after the activity by providing tests in the form of questions, assessing student performance in learning, and giving assignments. The teacher using PowerPoint as a teaching tool can increase students' understanding of Islamic religious education lessons